Pengembangan Media Pembelajaran Musikalisasi Puisi untuk Meningkatkan Kemampuan Belajar Siswa Kelas IX - Agnes Linda Astuti Gea; Ester Claryta Telaumbanua; Antonius Zendrato; Arozatulo Bawamenewi (Journal on Education, 2023)
This study was done to improve the skills of junior high school pupils employing poetry musicalization in educational media. This study's goals were to boost students' motivation and interest in poetry music, decrease learning process dullness, and especially assess the efficacy of poetry music medium.The Research and Development (R&D) technique was employed in this study as a roadmap for carrying out development. Researchers employed questionnaires for material expert validation and student response to gather data for their studies. The percentage of student test results falling under the category of "Very practical" achieved 85% based on the numbers that were immediately delivered in class. Number-based student test results indicate that poetry music media is practicable to utilize with a score of 95%, leading to the conclusion that it achieves 100% with a very practicable mix.